IMPLEMENTASI PELAKSANAAN PROGRAM KAMPUS MENGAJAR ANGKATAN 7 UNTUK MENINGKATKAN KEMAMPUAN LITERASI DAN NUMERASI DI SISWA SDK SUPILAPE - Putrini, Maria Anjelina; Bhoke, Wilibaldus; Bela, Maria Editha; Wewe, Melkior (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This research aims to improve the quality of learning, particularly in literacy and numeracy, for students with low abilities. The teaching campus program is designed to provide students with practical experience and opportunities for personal development outside the campus environment. The method used in this research is descriptive qualitative, with subjects consisting of 18 fifth-grade students from SDK Supilape. This study aims to implement the teaching campus program at SDK Supilape. Data collection techniques involved observation, interviews, and documentation, with results from observations being summarized. The implemented work programs include tutoring in mathematics, interactive video screenings, reading corners (literacy trees), math posters, technology adaptation (technology transformation for learning), and socialization to prevent the three major sins of education. The stages of implementation include preparation, observation, planning, and execution. The seventh batch of the teaching campus program has proven effective in improving literacy and numeracy skills among students at Sekolah Dasar Katolik Supilape, as shown by the research findings and discussions. The role of students in assisting peers and partnering with teachers has garnered many positive responses and impacts. Various programs that have been implemented are progressing according to plan, particularly in assisting students in literacy and numeracy, such as the reading corner program and additional numeracy hours, which both teachers and students have received well. The Minimum Competency Assessment (AKM) results show a significant increase in literacy and numeracy skills among fifth-grade students at SDK Supilape. In the pretest, 58% of students were in the sufficient category for literacy, while 41% were in the unfinished category for numeracy. After implementing the work programs, posttest results indicate that 72% of students are now in the good category for literacy, and 60% are in the sufficient category for numeracy. This improvement indicates that the implemented program has enhanced students' understanding of the material, demonstrating the effectiveness of the teaching methods.